Impact of Alcohol Consumption Restrictions on Negative Traffic Accidents on Lithuanian Highways - Kanišauskas, Vaidotas; Raudonis, Adomas (Jaunųjų mokslininkų darbai, 2022)
The article uses statistical data from the Lithuanian Road Police Service on traffic accidents, speeding, drinking and driving (DUI), and people injured in traffic accidents on Lithuanian highways, i.e., negative traffic accidents in the period of 2000–2018. The aim of the work is to analyse the dynamics of traffic collisions and circumstances related to them. To achieve this aim, the negative accident data recorded on Lithuanian highways was converted into a 1-mile (8 km) unified system by grouping roads according to their length: small, average, large, and the largest roads. Time series AR(1) models were found for most of the cases. By employing statistical methods, it was identified that the 2008 law restricting the sale and advertising of alcohol led to the following results: a reduction in traffic accidents and the number of intoxicated drivers on all roads, although at the same time there was an increase in speeding. The number of people injured on small roads has increased.
Keywords: highways; alcohol consumption restrictions; time series; statistical hypotheses